2013
DOI: 10.1016/j.str.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an HSA/FcRn Complex Reveals Recycling by Competitive Mimicry of HSA Ligands at a pH-Dependent Hydrophobic Interface

Abstract: The long circulating half-life of serum albumin, the most abundant protein in mammalian plasma, derives from pH-dependent endosomal salvage from degradation, mediated by the neonatal Fc receptor (FcRn). Using yeast display, we identified human serum albumin (HSA) variants with increased affinity for human FcRn at endosomal pH, enabling us to solve the crystal structure of a variant HSA/FcRn complex. We find an extensive, primarily hydrophobic interface stabilized by hydrogen-bonding networks involving protonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
170
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(189 citation statements)
references
References 56 publications
13
170
0
1
Order By: Relevance
“…6. Overall, our complex structure is in good agreement with that involving a HSA variant (V418M/T420A/ E505G/V547A) whose affinity for human FcRn was increased by ϳ300-fold (14). In particular, the r.m.s deviation for all atoms is 0.8 Å.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…6. Overall, our complex structure is in good agreement with that involving a HSA variant (V418M/T420A/ E505G/V547A) whose affinity for human FcRn was increased by ϳ300-fold (14). In particular, the r.m.s deviation for all atoms is 0.8 Å.…”
Section: Resultssupporting
confidence: 80%
“…Such a modified humanized IgG exhibited an ϳ2-4-and 4-fold increase in its serum half-life in human and cynomolgus monkeys, respectively (11,12). Other studies with human serum albumin (HSA) used modeling and crystallographic approaches coupled with mutagenesis to identify several important HSA residues, and pinpointed the crucial role played by its domain III (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the acidic endosome, positively charged histidine side chains can interact favorably with negatively charged side chains of FcRn; however, this affinity is greatly diminished at the neutral cell surface where IgG and SA are released into circulation. This hypothesis is supported by numerous genetic and mutagenesis studies as well as recent crystallographic data (12,13).…”
mentioning
confidence: 68%
“…Residues involved in interaction between human FcRn and IgG (Fc domain) or albumin (as described by Oganesyan et al, 2014, highlighted in yellow or in blue, respectively) are also shown. The sequence of human FcRn α-chain ECD was taken from Swiss Prot (P55899-1); Residue F44, identified by Oganesyan et al 29 as interacting with albumin, is residue E44 in this sequence and in the sequence of Schmidt et al 30 Dark blue = FcRn α-chain; pale blue = β2 M; magenta = 1519.g57 heavy chain; orange = 1519.g57 light chain; yellow = IgG Fc domain; red = 1519.g57 Fab’ binding epitope on FcRn.…”
Section: Resultsmentioning
confidence: 99%